2019
DOI: 10.1002/slct.201801773
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Properties of 1‐Hexadecanol‐Palmitic Acid Eutectic Mixture/Activated Carbon Composite Phase Change Material for Thermal Energy Storage

Abstract: In this study, a new kind of 1-hexadecanol-palmitic acid (HD-PA) binary eutectic mixture and the composite phase change materials (PCMs) composed of HD-PA absorbed into activated carbon (AC) pores with different mass percentage of 50, 55, 60, and 65% were prepared by vacuum impregnation method. The chemical structural, thermal stability and thermal durability of HD-PA/AC composite phase change materials (CPCMs) with different mass fraction of HD-PA was characterized by Fourier transformation infrared (FT-IR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The absorptions at 1472 and 1703 cm −1 were assigned to C–C vibrations and C═O stretching vibrations. Besides, 1296, 945, and 730 cm −1 were attributed to the bending vibration of in‐plane and out‐of‐plane, and in‐plane winging vibration of –OH in PA . Moreover, all of the characteristic absorption peaks from PA and diatomite were also displayed in the spectra of CPCMs.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The absorptions at 1472 and 1703 cm −1 were assigned to C–C vibrations and C═O stretching vibrations. Besides, 1296, 945, and 730 cm −1 were attributed to the bending vibration of in‐plane and out‐of‐plane, and in‐plane winging vibration of –OH in PA . Moreover, all of the characteristic absorption peaks from PA and diatomite were also displayed in the spectra of CPCMs.…”
Section: Resultsmentioning
confidence: 94%
“…The absorptions at 1472 and 1703 cm −1 were assigned to C-C vibrations and C═O stretching vibrations. Besides, 1296, 945, and 730 cm −1 were attributed to the bending vibration of in-plane and out-of-plane, and in-plane winging vibration of -OH in PA. 45,46 Moreover, all of the characteristic absorption peaks from PA and diatomite were also displayed in the spectra of CPCMs. Meanwhile, by comparing the absorption curves of PA and diatomite, no obvious peak shifts were observed in the absorption peaks of the CPCM1-CPCM7, which indicated that no chemical interaction existed and there was good compatibility between PA and diatomite.…”
Section: Ft-ir Analysismentioning
confidence: 93%
“…This phenomenon was caused by two reasons. Firstly, due to the strong van der Waals force, surface tension, capillary force as well as drag effect between PCMs and pore walls, the crystallization of PCMs in composites was somewhat intervened. Secondly, the lower content of PCMs in compounds affected the phase change temperature as well, which was similar to the PEG/NFMS and 1‐octadecanol/HPP composites system .…”
Section: Resultsmentioning
confidence: 99%
“…Ince et al [24] prepared a myristic acid (MA)/Gr composite material using MA as a thermal energy conversion carrier and Gr was served as a matrix material; their finding when the content of Gr in composite PCM at 2 %, the thermal conductivity increased 38 %. Hu et al [20] investigated 1-Hexadecanol-Palmitic acid (HD-PA)/AC composite developed by vacuum impregnation; the conclusion was that the heat exchange coefficient and thermal stability of the composites were enhanced. Putra et al [16] synthesized beeswax/ multi-wall CNTs composite PCM by the impregnation method; they found that adding multi-wall CNTs can improve the thermal performance and stability of solid and liquid beeswax.…”
Section: Introduction *mentioning
confidence: 99%